Seasonal characteristics and formation mechanism of the thermohaline structure of mesoscale eddy in the South China Sea - Zu, Yongcan; Sun, Shuangwen; Zhao, Wei; Li, Peiliang; Liu, Baochao; Fang, Yue; Samah, Azizan Abu (Springer Verlag, 2019)
The seasonal characteristics and formation mechanism of the thermohaline structure of mesoscale eddy in the South China Sea are investigated using the latest eddy dataset and ARMOR3D data. Eddy-centric composites reveal that the horizontal distribution of temperature anomaly associated with eddy in winter is more of a dipole pattern in upper 50 m and tends to be centrosymmetric below 50 m, while in summer the distribution pattern is centrosymmetric in the entire water column. The horizontal distribution of eddy-induced salinity anomaly exhibits similar seasonal characteristics, except that the asymmetry of the salinity anomaly is weaker. The vertical distribution of temperature anomaly associated with eddy shows a monolayer structure, while the salinity anomaly demonstrates a triple-layer structure. Further analysis indicates that the vertical distribution of the anomalies is related to the vertical structure of background temperature and salinity fields, and the asymmetry of the anomalies in upper 50 m is mainly caused by the horizontal advection of background temperature and salinity.